2020
DOI: 10.1111/pai.13151
|View full text |Cite
|
Sign up to set email alerts
|

Oral corticosteroids and asthma in children: Practical considerations

Abstract: When dealing with allergic disorders, pediatricians may prescribe systemic corticosteroids (CS) to treat several different diseases, such as asthma, allergic rhinitis, allergic conjunctivitis, angioedema, eczema, certain types of food allergy, and anaphylaxis, and to prevent a delayed response. The main effects for which they are used in allergy are their anti-inflammatory effect, their ability to relax smooth muscle cells, and their action on the allergic delayed response. In clinical practice, corticophobia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
2
1
0
Order By: Relevance
“…[41][42][43] Furthermore, OCS is widely used in emergency departments to relieve symptoms of wheeze, but studies have shown conflicting evidence of efficacy. [44][45][46] In our study, peripheral blood eosinophil levels were decreased in PW treated with OCS, demonstrating its antiinflammatory effect. Nevertheless, the difference in the expression of all 10 proteins was significant between PW and HC irrespective of OCS treatment in PW.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…[41][42][43] Furthermore, OCS is widely used in emergency departments to relieve symptoms of wheeze, but studies have shown conflicting evidence of efficacy. [44][45][46] In our study, peripheral blood eosinophil levels were decreased in PW treated with OCS, demonstrating its antiinflammatory effect. Nevertheless, the difference in the expression of all 10 proteins was significant between PW and HC irrespective of OCS treatment in PW.…”
Section: Discussionsupporting
confidence: 65%
“…Corticosteroids alter the balance between pro‐ and anti‐inflammatory proteins and suppress airway inflammation and are suggested to have the best effect in treating symptoms of wheeze in atopic individuals and children with severe wheeze 41–43 . Furthermore, OCS is widely used in emergency departments to relieve symptoms of wheeze, but studies have shown conflicting evidence of efficacy 44–46 . In our study, peripheral blood eosinophil levels were decreased in PW treated with OCS, demonstrating its anti‐inflammatory effect.…”
Section: Discussionsupporting
confidence: 52%
“…However, there is evidence that treatment with OCs, such as prednisolone, carries long-term health risks, such as growth impairment, pubertal disorders, hirsutism, diabetes, hypertension and many more. [86][87][88][89] A limitation of the economic analysis is the lack of health-related quality-of-life data for children experiencing exacerbations. Furthermore, previous evidence has suggested that hospitalisations may result in greater quality-of-life loss in children than in adults.…”
Section: Health Economicsmentioning
confidence: 99%